Penerapan Mirror Therapy terhadap Gangguan Mobilitas Fisik pada Pasien Stroke Iskemik di RS Mardi Rahayu Kudus - Dela Puspita Ernanda Sari; Sri Puguh Kristiyawati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Ischemic stroke occurs when a thrombus, embolus, or vascular stenosis disrupts blood supply to the brain, causing vessel rupture and blood leakage into the surrounding neuronal space. A common clinical symptom of stroke is hemiparesis, or muscle weakness on one side of the body. Non-pharmacological management, such as range of motion exercises using mirror therapy, can support rehabilitation. Mirror therapy is a form of motor rehabilitation that engages the patient's motor imagery. The mirror provides visual stimulation to the brain, particularly the cerebral motor nerves on both the affected and unaffected sides, to assist movement in limbs experiencing hemiparesis. This study used a case study method, implementing nursing care and evidence-based nursing practice. Over six consecutive days of intervention, mirror therapy led to increased muscle strength. Prior to the therapy, muscle strength was recorded at. After the therapy, muscle strength improved to. These results suggest that mirror therapy can serve as an effective rehabilitation strategy to address impaired physical mobility in patients with ischemic stroke.